An analysis of the relationship between corporate governance and risk management, and performance in the real estate industry - Ongwuttiwat, P. (2016)
Since financial crisis and Brexit caused the volatility in the housing sectors, the corporate and risk oversight at board level has been highlighted. This study investigates the relationship between the corporate governance and risk management, and firm performance in real estate sectors. Using the total samples of 198 UK and US real estate firms in 2015, the results suggested that the proportion of independent directors and the meetings of the boards are both significantly negatively associated with firm performance. Conversely, the board size significantly affects only for the firms in US with the same direction. This indicates that an increase in each board characteristic might not be beneficial for property firm performance. For the risk management aspects, the meeting of audit committee (AC) was found to have a negative impact on firm performance; in contrast, AC size was found no association. Interestingly, the existence of risk committee (RC) was found to have both positive and negative impacts on firm performance. Moreover, RC size was also found to be positive while RC outsider proportion is negatively associated with firm performance. However, RC meeting was found no relation. It is summarized that although the frequent meeting of AC cannot guarantee the enhancement of firm performance, having a risk committee in real estate sectors can enhance the firm profitability; nevertheless, it impairs the market value. An additional member of RC is also advantageous if the new member is an executive. Additionally, this study tried to examine the effects of country, and sub-sector. The results denoted that UK property firms perform greater than the US firms in most measures; only Tobin’s Q indicated the inverse result. Only board and AC meetings have the similar association with performance in both US and overall industry. Furthermore, the firms in Real Estate Investments and Services (Developers) sub-sector were also found to be greater in performance than the firms in Real Estate Investments Trusts (REITs). It is concluded that there might be the differences in regulations and investment strategies between UK and US, and event sensitivity between both sub-sectors.